Quantification and spatial distribution of salicylic acid in film tablets using FT-Raman mapping with multivariate curve resolution - Haslet Eksi-Kocak; Sibel Ilbasmis Tamer; Sebnem Yilmaz; Merve Eryilmaz; Ismail Hakkı Boyaci; Ugur Tamer (Elsevier, 2018)
In this study, we proposed a rapid and sensitive method for quantification and spatial distribution of salicylic acid in film tablets using FT-Raman spectroscopy with multivariate curve resolution (MCR). For this purpose, the constituents of film tablets were identified by using FT-Raman spectroscopy, and then eight different concentrations of salicylic acid tablets were visualized by Raman mapping. MCR was applied to mapping data to expose the active pharmaceutical ingredients in the presence of other excipients by monitoring distribution maps and combination of FT-Raman mapping with MCR enabled the determination of lower salicylic acid concentrations. In addition, the distribution of major excipient, lactose, was examined in the tablet form. A calibration curve was obtained by plotting the intensity of the Raman signal at 1635 cm−1 versus the concentration of salicylic acid and the correlation was found to be linear within the range of 0.5%-3.9% with a correlation coefficient of 0.99. The limit of detection for the technique was determined 0.35%. The ability of the technique to quantify salicylic acid in tablet test samples was also investigated. Keywords: Raman mapping, Multivariate curve resolution, FT-Raman spectroscopy, Salicylic acid